Influence of environmental gradients on the distribution of benthic resources available for shorebirds on intertidal mudflats of Yves Bay, France. (5th June 2016) - Philippe, Anne S.; Pinaud, David; Cayatte, Marie-Laure; Goulevant, Cyril; Lachaussée, Nicolas; Pineau, Philippe; Karpytchev, Mikhail; Bocher, Pierrick
Abstract: The case study of Yves Bay (Pertuis Charentais, France) highlighted links between environmental gradients ( i.e. sediment characteristics and emersion time) and prey distribution and availability for the two most numerous shorebird species overwintering in Yves Bay: the red knot Calidris canutus and the dunlin Calidris alpina . Two hundred and fifty-two stations were sampled on a predetermined 250 m regular grid covering the intertidal mudflats of this major wintering site in France for east-Atlantic migratory shorebirds. The distribution of principal benthic species abundance and biomass was modelled along two environmental gradients: sediment structure (particularly pronounced north–south sand-mud gradient) and emersion time. The effect of emersion time combined with sedimentary structure strongly explained abundances and biomasses of the main prey for C. canutus and C. alpina in the bay ( Cerastoderma edule, Hydrobia ulvae, Macoma balthica, Scrobicularia plana, and Nephtys hombergii) . This study highlighted prey species-specific spatial segregation/overlapping as well as spatial interferences in the trophic niche of the two shorebirds. Graphical abstract: Highlights: Yves Bay is an intertidal mudflat with an exceptional granulometric gradient. Available benthos resource for Calidris alpina and Calidris canutus is assessed. Densities of four dominant molluscs and one annelid species are mapped. Prey distribution are predicted along ET and MSG gradients. Potential trophic niches vary spatially between the shorebird species.